PENGARUH CEO TENUR, RAPAT DEWAN DIREKSI, EARNING POWER DAN PENGUNGKAPAN CSR TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Yani, Rizka; Yusrawati; Abrar (Journal Of Islamic Finance And Accounting Research, 2024)
This study is entitled The Influence of Ceo Tenur, Board of Directors Meetings, Earning Power and Disclosure of CSR on Profit Management in Transportation and Logistics Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This study aims to see the influence of CEO Tenur, Board of Directors Meetings, Earning Power and CSR disclosure on Profit Management. This research is a descriptive quantitative research. The population in this study are 28 transportation and logistics companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Samples were taken based on purposive sampling technique in order to obtain 28 companies that met the research criteria. Data analysis using multiple linear regression analysis. Based on the results of data analysis conducted by Ceo Tenur, Board of Directors Meetings, Earning power and CSR simultaneously affect Profit Management. Meetings of the Board of Directors and Earning Power have an effect on Profit Management while CEO Tenure and CSR have no effect on Earning Management